Personalized Learning untuk Generasi Z: Peluang dan Tantangan - Ruri Keristanti; Wahyuni Juliani; Muhammad Arifin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
The rapid technological changes in the 21st century have influenced how individuals learn, particularly among Generation Z, who have grown up as digital natives. This generation possesses unique characteristics such as dependence on technology, a desire for learning autonomy, and a tendency toward visual and interactive learning. These traits demand a more flexible, adaptive, and personalized educational approach. Personalized learning is considered one method capable of addressing these needs. The aim of this study is to explore the opportunities and challenges of implementing personalized learning for Generation Z. The research employed a qualitative methodology. To achieve this, a qualitative research approach was used, drawing data from various relevant literature sources. The Miles and Huberman model was applied as the data analysis methodology, which includes the processes of data reduction, data presentation, and drawing comprehensive conclusions. The results of the study indicate that personalized learning can enhance student motivation, engagement, and learning outcomes through the use of technology such as adaptive learning systems, digital platforms, and artificial intelligence. Additionally, personalized learning fosters the development of 21st-century skills such as independence, digital literacy, and problem-solving. However, challenges such as the digital divide, teacher readiness, and limitations of the national curriculum remain critical issues to be addressed. This study recommends strategies such as integrating technology and providing teacher training as initial steps toward the effective implementation of personalized learning.